Institutional arrangements for water reuse: assessing challenges for the transition to water circularity - Fayaz Riazi; Teresa Fidélis; Manuel Victor Matos; Maria Carolina Sousa; Filipe Teles; Peter Roebeling (Water Policy, 2023)
Water scarcity and security drive attention to water reuse in policy and business. However, water reuse may generate new water loops and challenge water governance with new and different types of water, risks, involved actors, and responsibilities. These challenges demand robust institutional arrangements related to water governance. This article assesses the institutional arrangements associated with four case studies in Spain, Italy, Croatia, and Israel. The findings reveal that the more diverse the water uses and users, the more challenges and risks, particularly those associated with institutional arrangements such as quality standards, sanctions, and conflict prevention, are likely to emerge. The weaknesses of governance models and regulations to deal with changes, uncertainties, and public resistance call for special attention to the design of the institutional arrangements before the adoption. Independent of the type of technology adopted, governance may be improved by ensuring internal and external water monitoring; integrating water management with spatial concerns; improving training, expert engagement, and civil society awareness; and reducing water reuse costs. In addition, alternative models that guarantee the efficiency of governance in attaining objectives and assuring the participation of new water users in the management of water reuse loops may also improve governance. HIGHLIGHTS Water recycling and reuse need robust institutional arrangements and legal measures.; Institutional arrangements hinder or drive the transition to water circular economy.; The more diverse the water uses and users, the more the risks, particularly those associated with institutional arrangements, are likely to emerge.; The analytical framework in this study contributed to a better understanding of the robustness of institutional arrangements.;